Relationship between Leg Strength and Balance and Lean Body Mass. Benefits for Active Aging - Castillo-Rodríguez, Alfonso; Onetti, Wanesa; Sousa Mendes, Rui; Chinchilla-Minguet, José Luis (Sustainability, 2020)
Physical activity (PA) can bring incalculable benefits to people throughout the aging process. The objective of this study was to determine the relationships between the leg and arm strength, body composition and balance of elderly people. Twenty-one people (9 men and 12 women) over 60 years of age voluntarily participated in this study. Bioimpedance tests were carried out to obtain body mass data, manual dynamometer tests and the lower limbs test were conducted to obtain strength values, and the stork balance stand test was conducted to assess static balance. As a result, medium-high correlation coefficients were obtained between the aforementioned dependent variables. The highest value corresponded to the relationship between the results of the dominant hand strength test (right hand in all participants) and the lean body mass (LBM) of the participant (R2 = 75%, p < 0.001). The results indicated that strength capacity, recorded by dynamometry, and balance ability have a direct relationship with the body composition of the subject, especially with their lean body mass. These data suggest that a greater lean body mass can provide greater strength and balance in the elderly, so it would improve or have greater duration the functionality and independence of the person, thereby justifying direct benefits in people and indirect benefits in public administrations that finance these social issues.
Keywords: aging; physical activity; sustainability; strength; health and wellness; body composition; Scopus; JCR